Enhancing Competency of Cybersecurity Through Implementation of the “CAPTURE THE FLAG” On College in Indonesia - Dudi Gurnadi Kartasasmita; F.G Cempaka Timur; Agus H.S Reksoprodjo (CV. AFDIFAL MAJU BERKAH, 2023)
Academic institutions encounter several challenges when it comes to determining the most effective pedagogical approaches for enhancing their students' proficiency in the domain of cybersecurity. Conversely, cybersecurity gamification, exemplified by Capture the Flag (CTF) events in the industry, is widely considered an appropriate avenue for fostering cybersecurity learning. This research endeavors to assess the effectiveness of employing gamification as an instructional tool to enhance cybersecurity competency within the college context. The study employs a quantitative research method, adopting an experimental approach with a pre-experimental design. The research findings reveal the following key points 1) the implementation of gamification resulted in a significant enhancement of students' competency in cryptography, web vulnerability, and overall cybersecurity, 2) the gamification experiment demonstrated a stronger influence on enhancing practical skills as opposed to theoretical knowledge, 3) the evaluation of gamification's effectiveness in augmenting cybersecurity competency yielded a medium level (medium-g) of efficacy, reaching 65.91%. Although the medium level of effectiveness was observed in the context of gamification, it should be acknowledged that gamification holds substantial potential for advancing cybersecurity competency. For the attainment of optimal improvement in cybersecurity skills, a consistent and regular integration of gamification is recommended, while concurrently addressing the three pillars of cybersecurity. Furthermore, the utilization of gamification also presents opportunities for cultivating cybersecurity incident handling capabilities and the simulation of cyberwarfare scenarios